Brief Report: Coordinated Modulation of Circulating miR-21 in HIV, HIV-Associated Pulmonary Arterial Hypertension, and HIV/Hepatitis C Virus Coinfection. (1st November 2015) - Parikh, Victoria N.; Park, Joseph; Nikolic, Ivana; Channick, Richard; Yu, Paul B.; De Marco, Teresa; Hsue, Priscilla Y.; Chan, Stephen Y.
Abstract : Abstract: Dysregulation of microRNA-21 (miR-21) is independently associated with HIV infection, pulmonary arterial hypertension (PAH), and hepatitis C virus (HCV) infection. To assess the expression of miR-21 in these overlapping comorbidities, we measured plasma miR-21 in HIV with and without PAH and then stratified by concomitant HCV infection. MiR-21 was increased in HIV and HIV-PAH versus uninfected subjects, but it did not differ between these groups. HIV/HCV coinfection correlated with even higher miR-21 levels within the HIV-infected population. These data reveal specific regulation of plasma miR-21 in HIV, HIV/HCV coinfection, and PAH and suggest that miR-21 may integrate complex disease-specific signaling in the setting of HIV infection. Abstract : Supplemental Digital Content is Available in the Text.